2020
DOI: 10.3390/w12010144
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-Meteorological Trends in the Yarlung Zangbo River Basin and Possible Associations with Large-Scale Circulation

Abstract: Climate change poses potential challenges to sensitive areas, such as high-elevation regions. The Yarlung Zangbo River (YLZR) basin is located in the southeast of the Qinghai-Tibetan Plateau. It contains large amounts of snow and numerous glaciers that are vulnerable to climate change. Based on daily observational data at 17 meteorological stations in and around the YLZR basin during 1957–2015, the variability of precipitation, air temperature, and streamflow were analyzed. The nonparametric Mann–Kendall test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…Annual precipitation in the upper reaches is approximately 200 mm, while that in the middle reaches is nearly 800 mm; the With increasing precipitation and temperature, regional vegetation grows well. These results reveal that the YZR basin is experiencing climate warming and wetting, which is consistent with the conclusions of Zhang et al (2020).…”
Section: Spatial Distributions Of Annual Hydrological Cycle Componentssupporting
confidence: 90%
“…Annual precipitation in the upper reaches is approximately 200 mm, while that in the middle reaches is nearly 800 mm; the With increasing precipitation and temperature, regional vegetation grows well. These results reveal that the YZR basin is experiencing climate warming and wetting, which is consistent with the conclusions of Zhang et al (2020).…”
Section: Spatial Distributions Of Annual Hydrological Cycle Componentssupporting
confidence: 90%
“…At local and regional scales, previous studies have been conducted on the connections between hydrological and environmental/climatic variations in arid and semi-arid regions. A study at China's Yarlung Zangbo River (YLZR) basin showed the negatively correlated relationship between the climatic indices, including Pacific decadal oscillation (PDO) and the multivariate El Niño-Southern Oscillation (ENSO) index (MEI)) and precipitation, annual average temperature, and the streamflow of selected hydrological stations [67]. Similarly, this negative relationship between precipitation and ENSO indices was also found for Jana and Karan Islands in the nearshore Saudi Arabia area [36].…”
Section: Discussionmentioning
confidence: 96%
“…No autocorrelation was found in the SP trend at any station. These methods, linear least square, prewhitening, and Mann Kendall, are widely used to analyze rainfall data within time series [6,10,[42][43][44][45][46].…”
Section: Methodsmentioning
confidence: 99%